2008
DOI: 10.1007/s00784-007-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selective caries removal in deciduous teeth by a fluorescence feedback-controlled Er:YAG laser in vivo

Abstract: This study investigated the ability and efficacy of an Er:YAG laser with a fluorescence feedback system for caries removal in deciduous teeth. Seventy-nine carious lesions were excavated using a fluorescence-controlled Er:YAG laser. Endpoint of treatment was defined by emission of fluorescence from the dentine surface below the pre-selected threshold level of 7 units and the subsequent termination of Er:YAG laser radiation. Dentine samples were obtained from the cavity floor, and viable counts of both Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
1
16
0
10
Order By: Relevance
“…Dokuya temas etmeden çalıĢma zorunluluğunun getirdiği kontrol kaybı, floresans geribildirim özelliği ile kombine edilmiĢ Er:YAG lazerler ve Er, Cr:YSGG lazerlere eklenen sesli uyarı sistemi ile giderilmeye çalıĢılmıĢtır. [51][52][53] Çürüğü uzaklaĢtırmak amacıyla kullanılan CO 2 , Nd:YAG ve Erbium lazerler sağlıklı doku ile çürük dokunun ayırt edilmesini sağlarken, enfekte ve etkilenmiĢ dentin ayrımını sağlayamamaktadır. Bu nedenle daha selektif yaklaĢımlar için gerekli dalga boyları ve lazer tipleri geliĢtirilmeye çalıĢılmaktadır.…”
Section: çüRüğü Uzaklaģtırmada Selektif Yaklaģımlarunclassified
“…Dokuya temas etmeden çalıĢma zorunluluğunun getirdiği kontrol kaybı, floresans geribildirim özelliği ile kombine edilmiĢ Er:YAG lazerler ve Er, Cr:YSGG lazerlere eklenen sesli uyarı sistemi ile giderilmeye çalıĢılmıĢtır. [51][52][53] Çürüğü uzaklaĢtırmak amacıyla kullanılan CO 2 , Nd:YAG ve Erbium lazerler sağlıklı doku ile çürük dokunun ayırt edilmesini sağlarken, enfekte ve etkilenmiĢ dentin ayrımını sağlayamamaktadır. Bu nedenle daha selektif yaklaĢımlar için gerekli dalga boyları ve lazer tipleri geliĢtirilmeye çalıĢılmaktadır.…”
Section: çüRüğü Uzaklaģtırmada Selektif Yaklaģımlarunclassified
“…However, the adjustment of laser energy density in commercial equipments is sometimes difficult to promote the selective ablation of infected dentin and in order to preserve the affected dentin, and the clinical results still depend on the experience and knowledge of the professional, added to the use of manual instruments for correct diagnosis of remaining tissue. In fact, clinical trials report the well acceptance of patients (Dommisch et al, 2008;Krause et al, 2008), the maintenance of pulp vitality and marginal seal, the good quality of restorations and the absence of secondary caries even after two years (Yazici et al, 2010). Also, it is reported that these lasers can fulfill the requirements of Minimal Invasive Dentistry, due to the possibility of conservation of the sound tissue structure during caries removal and to the possibility of surface decontamination of affected dentin (Kornblit et al, 2008).…”
Section: The Use Of Erbium Lasers For Caries Therapymentioning
confidence: 99%
“…To determine an end point for caries removal, there are some equipments that associate Er:YAG laser irradiation to the diagnosis by laser fluorescence (Dommisch et al, 2008;Eberhard et al, 2008;Jepsen et al, 2008;Krause et al, 2008;). The essential principle of this application is that the fluorescence of sound tissue differs from the fluorescence of carious tissue due to the variation in chemical composition, such as the presence of proteins, bacteria and other contents.…”
Section: The Use Of Erbium Lasers For Caries Therapymentioning
confidence: 99%
See 2 more Smart Citations